Assessment of nutritional status amongst bihor tribe childrens residing in Dharamjaigarh block of Raigarh district (C.G.), India - Somawar, Badri Narayan Rao; Phuljhale, Sharja (International Journal of Research in Medical Sciences, 2017)
Background: Despite rapid economic development along with increase in food production in recent decades and several nutritional intervention programmes in operation since the last three decades, childhood under nutrition remains an important public health problem in India. The burden of under nutrition appears particularly high among rural and Indigenous tribal populations. “Birhor” tribal community of Dharamjaigarh block, Raigarh district has long remained a separate entity in terms of the demographic, health and socioeconomic characteristics. By any standard measurement of social improvement the “Birhor” tribal communities can be registered as one of the most vulnerable section of society. The social and economic backwardness has always been responsible for poor health status, high incidence of low birth weight, infant and child mortality among these groups. In India, many recent studies have been conducted on the nutritional status of preschool children and have revealed a high rate of malnutrition. With the above background, the present study was conducted to assess the nutritional status in tribal children’s in the study area. Methods: The present cross sectional study was carried out in Dharamjaigarh block of Raigarh district. The study was conducted from January 2013 to June 2014. 63 children of 0-3.5 year’s age group from 148 families of 15 villages of Primitive Birhor Tribe were randomly selected where the population of Birhor tribe is more as shown in map. Pretested structured questionnaire was used to gather data from parent/head of family by door to door visit of every household Nutritional assessment was done by clinical examination and anthropometric measurement using standard equipment and procedures. As per Pretested structured proforma general information of every child was noted. Age was confirmed either by calendar of local events or from registers of aganwadi worker and recorded in complete month. Other relevant information was also noted. Results: Out of 63 children studied Over all 16(51.6 %) of female children were malnourished when compare to 10 (31.3%) of male children. Out of total malnourished children 19 (30.2%) found moderately malnourished and 7 (11.1%) severely malnourished. Most of the cases of stunting were >1 year of age 29/38 (76.3%).Most of the cases of stunting were females (60.5%). Most of the wasting cases were above 12 months of age 9(90%), p<0.0001, statistically significant. Most of the wasting cases were females (60%) than males (40%). Conclusions: Present study demonstrates that children in this tribe are at very high risk. Steps are needed to improve the same.